Obesity Is a Marker of Reduction in QoL and Disability. (12th March 2012) - Sirtori, Anna; Brunani, Amelia; Villa, Valentina; Berselli, Maria Elisa; Croci, Marina; Leonardi, Matilde; Raggi, Alberto
Abstract : The purpose of this paper is to verify the association between outcome measures of health-related quality of life (HRQoL) and disability, BMI, gender, and age. Adult obese patients were clustered using HRQoL (IWQoL-Lite) and disability (WHO-DAS II) scores into three groups: mild, moderate, and high. One-way ANOVA with Bonferroni post hoc test was used to evaluate differences in age and BMI between subjects from different clusters, contingency coefficient to test the relationship between cluster groups and gender. In total, 117 patients were enrolled: subjects with higher disability and HRQoL decrement were older and had higher BMI. Women were more likely to present moderate disability and reduction in HRQoL, while men more likely presented mild disability and HRQoL reduction. Our data further confirm the connection between disability and HRQoL, high BMI and older age. These data obtained with outcomes measures might better address rehabilitation programs.